Narrativas sobre la reestructuración familiar de un grupo de mujeres que perdieron a su pareja por consecuencia del COVID-19 - Gutiérrez Montiel, Claudia Patricia (Universidad Antonio Nariño, 2022)
The objective of this study was to analyze the narratives about the restructuring of a group of women who lost their partner as a result of COVID-19. The type of research used was qualitative. An unstructured interview was used to collect the information. The participants were four women who lost their partner as a result of COVID 19